2006
DOI: 10.1111/j.1460-9568.2005.04574.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization and function of pre‐ and postsynaptic kainate receptors in the rat globus pallidus

Abstract: Kainate receptors (KARs) are widely expressed the basal ganglia. In this study, we used electron microscopic immunocytochemistry and whole-cell recording techniques to examine the localization and function of KARs in the rat globus pallidus (GP). Dendrites were the most common immunoreactive elements, while terminals forming symmetric or asymmetric synapses and unmyelinated axons comprised most of the presynaptic labeling. To determine whether synaptically released glutamate activates KARs, we recorded excitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 67 publications
(150 reference statements)
2
38
1
Order By: Relevance
“…The localization of KA receptors at the EM level has been studied in the striatum and GP (Charara et al, 1999;Kieval et al, 2001;Kane-Jackson and Smith, 2003;Jin and Smith, 2005;Jin et al, 2006), but not in other basal ganglia. In the monkey striatum, pre-and postembedding immunogold methods have revealed that the largest proportion of GluR6/7 and KA2 plasma membrane-bound subunits is located at extrasynaptic sites, while only one third is located at glutamatergic synapses ), a strikingly different pattern from that of AMPA and NMDA receptors distributions (Bernard et al, 1997;Bernard and Bolam, 1998;Fujiyama et al, 2004).…”
Section: Ionotropic Receptorsmentioning
confidence: 99%
“…The localization of KA receptors at the EM level has been studied in the striatum and GP (Charara et al, 1999;Kieval et al, 2001;Kane-Jackson and Smith, 2003;Jin and Smith, 2005;Jin et al, 2006), but not in other basal ganglia. In the monkey striatum, pre-and postembedding immunogold methods have revealed that the largest proportion of GluR6/7 and KA2 plasma membrane-bound subunits is located at extrasynaptic sites, while only one third is located at glutamatergic synapses ), a strikingly different pattern from that of AMPA and NMDA receptors distributions (Bernard et al, 1997;Bernard and Bolam, 1998;Fujiyama et al, 2004).…”
Section: Ionotropic Receptorsmentioning
confidence: 99%
“…Although not universally present, functional postsynaptic KARs have been shown to be present in a variety of cell types such as cerebellar granule cells and Golgi cells (Bureau et al, 2000), retinal bipolar cells (DeVries and Schwartz, 1999), neurons of the superficial dorsal horn (Li et al, 1999), lateral superior olive (Vitten et al, 2004), motor & somatosensory cortex (Kidd and Isaac, 1999, Ali, 2003, Eder et al, 2003, the amygdala , the anterior cingulate cortex (Wu et al, 2005), the globus pallidus (Jin et al, 2006), and a variety of neurons in the hippocampus (Castillo et al, 1997, Vignes and Collingridge, 1997, Cossart et al, 1998, Frerking et al, 1998, Frerking et al, 1999, Cossart et al, 2002. In accordance with these previous studies, KAR mediated EPSCs in the mEC were defined by their resistance to 100 μM GYKI 52466 or 1 μM NBQX, their small amplitude and slow kinetics, the ability to summate during high frequency stimulation, and their inhibition by 10-50 μM CNQX.…”
Section: Postsynaptic Kainate Receptors Of the Mecmentioning
confidence: 99%
“…These receptors have been shown to both mediate and modulate synaptic transmission in both the central and peripheral nervous system (for reviews see (Chittajallu et al, 1999, Frerking and Nicoll, 2000, Lerma et al, 2001, Lerma, 2003, Lerma, 2006, Pinheiro and Mulle, 2006). Regarding the mediation of synaptic transmission, functional postsynaptic KARs have been demonstrated in a variety of cell types (Castillo et al, 1997, Vignes and Collingridge, 1997, Cossart et al, 1998, Frerking et al, 1998, DeVries and Schwartz, 1999, Kidd and Isaac, 1999, Li et al, 1999, Bureau et al, 2000, Cossart et al, 2002, Ali, 2003, Eder et al, 2003, Vitten et al, 2004, Wu et al, 2005, Jin et al, 2006 and may impose unique integrative properties to neurons (Frerking and Ohliger-Frerking, 2002). Furthermore, the expression of postsynaptic KARs has been shown to be restricted in a cellular and subcellular manner.…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular release of ATP was almost completely blocked by U-73122, a phospholipase C inhibitor; thapsigargin, a Ca 2+ -ATPase inhibitor; and BAPTA / AM, an intracellular Ca 2+ chelator. Furthermore, the release of ATP was markedly reduced by N-ethylmaleimide (NEM), a G-protein inhibitor (24,25) (Fig. 2A).…”
Section: Involvement Of Ins(145)p 3 Signals In the Release Of Atp Wmentioning
confidence: 99%